THE GROWTH RATE OF LENGTH DIMENSION OF SWAMP BUFFALO IN CENTRAL LOMBOK REGENCY - Purwanti, Ni Luh Lasmi; Sampurna, I Putu; Susari, Ni Nyoman Werdi (Buletin Veteriner Udayana, 2021)
This study aims to determine the growth rate of length dimension of male and female swamp buffalo ( Bubalus bubalis ) in Central Lombok. This study measured 54 swamp buffaloes (27 male and 27 female) from Central Lombok Regency. The age of buffalo is measured from the age of nine months to 20 months, and each 3 male and female swamp buffalo is measured at the same age. The measurement of body length dimensions carried out every month as many as 18 buffalo consisted of nine male and nine females. So that measurements are made for 3 months. The data obtained were analyzed by multivariant and power regression. The results of the multivariant analysis showed that the growth rate of male buffalo body dimensions was significantly different from the females (P<0.05) in Central Lombok Regency. The results of the power regression analysis showed that the correlation coefficients of each dimension of head, horn, ear, neck, body and male and female swamp buffalo were significantly different (P<0.05). The earliest dimensions of the male buffalo body growth are the dimensions of the head length then followed by body length, tail length, neck length, ear length, and the last is the length of the horn. While the longest dimensions of the female buffalo mud body grow are dimensions of head length, body length and ear length, then followed by tail length, neck length and finally horn length which has a later growth rate.